Vegetating thought and sensitivity for possible planthroposcenes (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article drew on the sensitive experiences and concepts embodied in the course Ecologies of attention: drifts between sewing and cultivation, taught by professors Virgínia Kastrup (UFRJ) and Mariana Guimarães (CAp-UFRJ) at the Institute of Psychology at UFRJ, during the first semester of 2025. Instigated by Evando Nascimento's work, O pensamento vegetal (2021), and more specifically by the semantics of the verb "to vegetate", the article proposed a positive rehabilitation of the term, countering its colonial meaning, as inspired by Antônio Bispo dos Santos (2023). The article explored how we can learn from and conspire with plants in search of possible planthroposcenes (Myers, 2021).
Keywords: to vegetate; thought; sensitivity; planthroposcene